Analisis Rencana Pelaksanaan Pembelajaran (RPP) Biologi Berkarakter Kelas XI SMAN Untuk Standarisasi RPP Di Kota Padang Panjang - Suci, Aprila Insan; Mulyati, Mulyati; Risdawati, Renny (Pendidikan Biologi, 2013)
ABSTRACT  Education is one of the efforts in the learning process and the learning process , in order to achieve the process there are teacher educators . Teacher in charge of educating , teaching , guiding , directing , training , assessing , and evaluating . In addition , teachers are also expected to design a lesson plan (RPP). High school teacher in Padang Panjang city made lesson plan together in MGMP. The purpose of this study was to determine the learning implementation  plan  (RPP)  in  Senior  High  School  in  the  city  of  Padang  Panjang  .This research is a descriptive study by collecting RPP SMAN biology teacher in Padang Panjang and analyze questionnaire based IPKG. Samples were taken in total sampling. Based on the research results obtained on the completeness of the components of plan ( RPP ) is 61 % and that there is no 39 % , while the implementation of learning outcomes assessment plan ( RPP ) is 80.7 % . With the results of the analysis showed that RPP grade biology teacher at SMAN Padang Panjang city is a standard for use in the learning process.